Prognostic significance of CD20 expression and Epstein‐Barr virus (EBV) association in classical Hodgkin lymphoma in Japan: A clinicopathologic study. (July 2014) - Elsayed, Ahmed Ali; Asano, Naoko; Ohshima, Koichi; Izutsu, Koji; Kinoshita, Tomohiro; Nakamura, Shigeo
<x xml:space="preserve">Abstract</x> To investigate the clinicopathological significance of CD20 expression and Epstein‐Barr virus (EBV) association in Hodgkin and Reed–Sterberg cells of classical Hodgkin lymphoma (CHL), CD20 expression and EBV positivity (by EBER in situ hybridization) were investigated in 389 CHL patients in Japan. They included 74 CD20‐positive cases (19%) and 315 CD20‐negative cases (81%). CD20‐positive cases showed significantly older age at onset (P = 0.018) and higher association with EBV (P = 0.002). Multivariate analysis identified EBV‐positivity (but not CD20‐positivity), presence of B symptoms, thrombocytopenia, elevated serum lactate dehydrogenase and performance status >1 as poor prognostic factors for overall survival (OS). We constructed a new prognostic model with these five factors classifying patients into three groups: low risk, 0–1 adverse factor; intermediate risk, 2–3 factors; high risk, 4–5 factors. This prognostic model could stratify the prognosis of CHL patients (P < 0.0001). For 144 patients (58%) classified into the low‐risk group, the 5‐year OS was 91%. For 92 patients (37%) in the intermediate group, the 5‐year OS was 66%; for 11 patients (5%) in the high‐risk group, the 5‐year OS was 36%. In conclusion, EBV is identified as an independent poor prognostic factor for CHL patients. Therefore, examination of EBV association in CHL is recommended as routine pathologic practice especially in countries where EBV infection prevails.